Motivations, attitudes for choosing dental profession and preferred dental specialties amongst Turkish dental students - ŞEN YAVUZ, BETÜL; KARGÜL, BETÜL (My University, 2021)
AIM: The aim of the study was to investigate the influential factors for choosing dentistry, their thoughts about the profession, their expectations for the future and their thoughts about the specialisation of dental students from all grades in the School of Dentistry, Marmara University. MATERIALS AND METHODS: Socio-demographic information, influential factors the choice of profession, thoughts and expectations about dentistry, and thoughts about the specialisation were evaluated in the questionnaire that included different question types in four separate sections. Chi-square test was used to assess the relationship between categorical variables, and multiple linear regression was performed to examine the combined effects of variables that influence the always dream of becoming a dentist. RESULTS: 462 of the 471 participants from all grades who agreed to participate in the study completed the questionnaire with a response rate of 98.1%. It was seen that the students' clinical experience made differences in almost half of their motivational sources for choosing dentistry and their views on future opinions and expectations (p < .05). In addition to clinical experience, gender also made a statistically significant differences in almost all answers in the students' opinions about specialisation (p < .05). CONCLUSION: From the results of the study, the majority of Turkish dental students were self-motivated compared to familial and environmental factors for choosing dentistry as a career. The career motivations of them seemed to be associated with the socioeconomic aspects of dentistry, whereas the perceptions regarding the future of dentistry seemed to be associated with the need for postgraduate education.
Keywords: career choice; clinical experience; dental specialties; dental students; paediatric dentistry